Sulfur amino acid requirement of the finishing pig - Trotter, M.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A growth and two nitrogen retention studies were conducted to determine the sulfur amino acid requirement of the finishing pig. Adding 0.10% DL-methionine to a 9.0% protein semi-purified basal diet containing 0.14% total sulfur amino acids significantly (P<.05) increased nitrogen retention, but further additions of DL-methionine had no beneficial effect. Daily gain was not significantly affected by adding DL-methionine to the basal diet, suggesting that the finishing pig has a lower sulfur amino acid requirement for daily gain than is essential for maximum nitrogen retention. These results suggest that the sulfur amino acid requirement of the finishing pig fed a 9.0% protein diet does not exceed 0.24% of the diet.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Sulfur amino acid; Finishing pig; DL-methionine; Protein